Treatment with the dual-incretin agonist DA-CH5 demonstrates potent therapeutic effect in a rat model of Wolfram Syndrome - Jagomäe, Toomas; Gaur, Nayana; Seppa, Kadri; Reimets, Riin; Pastak, Marko; Plaas, Mihkel; Kaasik, Allen; Vasar, Eero; Plaas, Mario (Frontiers in Endocrinology, 2023)
Aim: Wolfram Syndrome (WS) is a rare condition caused by mutations in Wfs1, with a poor prognosis and no cure. Mono-agonists targeting the incretin glucagon-like-peptide 1 (GLP-1) have demonstrated disease-modifying potential in pre-clinical and clinical settings. Dual agonists that target GLP-1 and glucose-dependent insulinotropic polypeptide (GIP-1) are reportedly more efficacious; hence, we evaluated the therapeutic potential of dual incretin agonism in a loss-of-function rat model of WS. Methods: Eight-month-old Wfs1 knock-out (KO) and wild-type control rats were continuously treated with either the dual agonist DA-CH5 or saline for four months. Glycemic profile, visual acuity and hearing sensitivity were longitudinally monitored pre-treatment, and then at 10.5 and 12 months. Pancreata and retina were harvested for immunohistological analysis. Results: DA-CH5 therapy reversed glucose intolerance in KO rats and provided lasting anti-diabetogenic protection. Treatment also reversed intra-islet alterations, including reduced endocrine islet area and β-cell density, indicating its regenerative potential. Although no rescue effect was noted for hearing loss, visual acuity and retinal ganglion cell density was better preserved in DA-CH5-treated rats. Conclusions: We present preclinical evidence for the pleiotropic therapeutic effects of long-term dual incretin agonist treatment; effects were seen despite treatment beginning after symptom-onset, indicating reversal of disease progression. Dual incretins represent a promising therapeutic avenue for WS patients.